Perspektywa porównawcza rezygnacji ze szkoły w sytuacjach ryzyka nastoletnich uczniów w beduińskim systemie oświaty w regionie Negew - Abu Ajaj, Ibraheem (Studia Edukacyjne, 2020)
The phenomenon of dropping out of students from the educational system in Israel has been steadily increasing in recent years. Many research studies that addressed the phenomenon of dropping out indicated an increase in the percentage of students dropping out from the Bedouin educational system in the Negev. The present research study examines the tendency to drop out of adolescents in situations of risk in the recognized Bedouin communities in comparison to adolescents in situations of risk in the unrecognized Bedouin communities with regard to different demographic variables and the involvement of the parents. These adolescents are daily exposed to emotional and social difficulties and do not receive adequate research attention. The issue of the dropping out of adolescents is an acute problem with considerable significance in the Arab sector in general and in the Bedouin communities in particular. The research study examines the situation today, the situation of the adolescents who are dropping out, their problems, and the reasons that led them to dropping out, in a comparison between the two types of Bedouin communities. The research findings will indicate possible ways for the reduction of the multidimensional phenomenon of dropping out. In light of the large gaps that exist between the educational system in Jewish society and the educational system in Bedouin society, the research study emphasizes that there is a direct impact on the Bedouin educational system, which directly influences the dropping out of students from the educational system in general and the dropping out of students in situations of risk. The sample consisted of 90 adolescents in situations of risk, 45 adolescents from recognized communities and 45 adolescents from unrecognized communities from different schools. In light of the examination of the research findings, it appears that the involvement of the parents influences the drooping out significantly. This finding indicates the importance of parental involvement in the school and its importance for the future of the children. In other words, a Bedouin child with an involved family will likely remain in the educational framework, while a Bedouin child whose parents are disconnected from his studies has increased chances to drop out of the educational system.